Community mental health nurses' experience of decentralised and integrated psychiatric-mental health care services in the Southern mental health region of Botswana (part 1) - M.K. Maphorisa; M. Poggenpoel; C.P.H. Myburgh (AOSIS, 2002)
Since the inception of the decentralisation and integration of psychiatric mental health care services into the general health care delivery system in Botswana, there has never been a study to investigate what community mental health nurses are experiencing due to the policy. Many of these nurses have been leaving the scantily staffed mental health care services in increasing numbers to join other sectors of health or elsewhere since the beginning of the implementation of the policy. During the research study, phenomenological in-depth interviews were conducted with three groups of 12 community mental health nurses altogether. An open central question was posed to each group followed by probing questions to explore and describe these nurses' experience of the decentralisation and integration of psychiatric-mental health care services. After the data was analysed, related literature was incorporated and guidelines for advanced psychiatric nurses were formulated and described to assist these nurses to cope with the decentralisation and integration of psychiatric-mental health care services. The guidelines were set up for the management of the community mental health nurses who are experiencing obstacles in the quest for mental health which also interfere with their capabilities as mental health care providers.